Examining the Psychosocial and Behavioral Factors Associated with Adolescent Engagement in Multiple Types of Cyberdeviance: Results from an Australian Study. - Brewer, Russell; Whitten, Tyson; Logos, Katie; Sayer, Morgan; Langos, Colette; Holt, Thomas J.; Cale, Jesse; Goldsmith, Andrew (Journal of Child & Family Studies, 2023)
Research has shown that psychosocial and behavioral factors are associated with engagement in a range of deviant behaviors across offline settings. To date, however, very little research has explored the impact of these factors in online contexts. This article addresses this gap by examining the psychosocial and behavioral factors associated with common types of adolescent cyberdeviance. This is accomplished through an empirical study of 327 adolescents enrolled in a high school located in a large Australian city. The study assesses various aspects of psychosocial and behavioral functioning using the Strengths and Difficulties Questionnaire (total difficulties, internalizing problems, externalizing problems, prosocial behavior), as well as numerous types of cyberdeviance relevant to young people, including cyberfraud, cyberhate, cyberviolence, sexting, digital piracy, hacking, and cyberbullying. A series of multivariate logistic regression analyses were conducted to demonstrate the association between psychosocial and behavioral difficulties and various types of cyberdeviance, independent of gender, school grade, socioeconomic status, and engagement in offline delinquency. Results indicate that total difficulties, internalizing problems, and externalizing problems were significantly associated with greater likelihood of engagement in most types of cyberdeviance examined in this study, whereas prosocial behavior was associated with a lower likelihood of engagement in digital piracy only. A discussion of the findings highlights the importance of understanding these factors in a digital context, as well as demonstrating the need to account for them when designing targeted interventions. Highlights: Identifying evidence-based approaches to help develop effective interventions for young people is critical due to the potentially serious social and economic harms associated with many types of cyberdeviance. A survey of Australian adolescents examined the relationship between types of cyberdeviance and various psychosocial and behavioral factors. Internalizing and externalizing problems, as well as prosocial behaviors, were all differentially associated with engagement in various types of cyberdeviance. Further research regarding the development of interventions that target internalizing and externalizing problems is proposed.